Interações metodológicas e interrelações humanas: alicerçando a transdisciplinaridade no campo da saúde no trabalho - Schmidt, Maria Luiza Gava [UNESP] (My University, 2012)
This article provides reflections and discussions about the importance of human interactions and methodological interrelations to substantiate the integrity in the transdisciplinary process in teams that operate in health area. Should be taken as reference the Complexity Theory of Edgar Morin, the logic transdisciplinary of Basarab Nicolescu and the formation groups principles based on the Socionomic Theory of Jacob Levy Moreno. It was concluded that the complexity of the methodologies in the field of workplace health, are influenced by factors that intersect between the scientific interaction and human interrelationships, which allow the transdisciplinary construction. However, the constructions requires the development of professionals in their areas and in their relationship with others as a way of supporting the perspective of transdisciplinarity, ie, interaction, in which different individuals are interrelated with the methodologies and providing articulations and coconstructions from which actualize the transformations.

Este artigo traz reflexões e discussões acerca da importância das interações metodológicas e interrelações humanas para alicerçar a integralidade no processo de transdisciplinaridade em equipes que atuam no campo da saúde no trabalho. Toma-se como referência a Teoria da Complexidade de Edgar Morin, a lógica transdisciplinar de Basarab Nicolescu e os princípios de constituição de grupo da Teoria Socionômica de Jacob Levy Moreno. Conclui-se que a complexidade das metodologias do campo da saúde no trabalho, são influenciadas por fatores que se entrecruzam entre as interações científicas e as interrelações humanas, que permitem a construção transdisciplinar. No entanto, essa construção requer o desenvolvimento dos profissionais nos seus papéis bem como na sua relação com o outro, como forma de alicerçar a perspectiva da transdisciplinaridade, ou seja, uma ação interprofissional, na qual diferentes sujeitos se intersubjetivam, interagem metodologias, permitem articulações e co-construções e dessa co-construção efetivam as transformações.
Methodological interaction and inter human relations: basis the transdisciplinarity in the health field at work
Keywords: Health at Work; Integrality; Transdisciplinarity; Socionomic Theory; Complexity Theory; Saúde no trabalho; Integralidade; Transdisciplinaridade; Teoria socionômica; Teoria da complexidade